Medication Adherence and Contributing Factors Among Type 2 Diabetes Patients at Adama Hospital Medical College in Eastern Ethiopia - Tewodros Yosef MPH; Dejen Nureye MSc; Eyob Tekalign MSc; Elias Assefa MPH; Nigusie Shifera MPH (SAGE Publishing, 2023)
Introduction Good glycemic control and preventing early complications are the ultimate targets of diabetes management, which depends on patients' adherence to regimens. Even though highly potent and effective medications have been developed and manufactured with astonishing advancement over the past few decades, excellent glycemic control has remained elusive. Objective This study aimed to assess the magnitude and factors associated with medication adherence among type 2 diabetes (T2D) patients on follow-up at Adama Hospital Medical College (AHMC) in East Ethiopia. Methods A hospital-based cross-sectional study was conducted among 245 T2D patients on follow-up at AHMC from March 1 to March 30, 2020. Medication adherence reporting scale-5 (MARS-5) was utilized to collect information regarding patients' medication adherence. The data were entered and analyzed using SPSS (Statistical Package for Social Sciences) version 21. The level of significance was declared at a p -value of  < .05. Results Of the 245 respondents, the proportion of respondents who adhere to diabetes medication was 29.4%, 95% CI [confidence interval] (23.7%-35.1%). After adjusting for khat chewing and adherence to blood glucose testing as confounding factors, being married (AOR [adjusted odds ratio]  =  3.43, 95%CI [1.27-4.86]), government employee (AOR  =  3.75, 95%CI [2.12-7.37]), no alcohol drinking (AOR  =  2.25, 95%CI [1.32-3.45]), absence of comorbidity (AOR  =  1.49, 95%CI [1.16-4.32]), and having diabetes health education at health institution (AOR  =  3.43, 95%CI [1.27-4.86]) were the factors associated with good medication adherence. Conclusion The proportion of T2D patients who adhere to medication in the study area was remarkably low. The study also found that being married, government employee, no alcohol drinking, absence of comorbidity, and having diabetes health education at a health institution were the factors associated with good medication adherence. Therefore, imparting health education on the importance of diabetes medication adherence by health professionals at each follow-up visit should be considered. Besides, awareness creation programs regarding diabetes medication adherence should be considered using mass media (radio and television).